ENCAPSULATION OF EGGSHELL POWDER TO CALCIUM ALGINATE FOR ADSORPTION METHYLENE BLUE - YORO PARLINDUNGAN ( NIM : 90514009), JOHN
One of the major problems concerning textile industrial wastewater is colored effluent. Discharging even small amount colored wastewater is not only damaging the aesthetic nature of receiving streams, but also it can affect aquatic life and food webs due to the carcinogenic and mutagenic effects of synthetic dyes. Methylene blue (MB) is one of the dyes are widely used in textile industries and become a big concern in the waste treatment process because it is difficult to be decomposed in the nature and dangerous to the environment. Therefor studi of adsorption of methylene blue (MB) from aqueous solution using calcium alginate (CA), powdered eggshell (SCKT), powdered eggshell was encapsulated in calcium alginate (CA-SCKT) by varying the parameters such as pH, agitation time, dye concentration, and adsorbent dose was studied with the batch method. The adsorbents have been characterized using Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). It was studied that the optimum methylene blue adsorption onto SCKT, CA, and CA-SCKT occurred at contact time of 2 hours. The optimum adsorbent dosage of 0.05 g pH 6-7 and initial concentration of 400 ppm. The percentage of methylene blue adsorbed by SCKT, CA, and CA-SCKT and adsorption capacity in optimum condition were 25.07 % and 10.03 mg/g; 66.03 % and 26.41 mg/g and 73.45 % and 29.38 mg/g respectively. The pseudo-first and pseudo-second order were used investigate kinetic model for adsorption process. The adsorption of MB on the adsorbents follows the pseudo-second order equation. CA and CA-SCKT adsorbent are reusable after contacted with hydrochloric acid 0.1 M.